Timing of Early-Life Stress and the Development of Brain-Related Capacities - Hambrick, Erin P.; Brawner, Thomas W.; Perry, Bruce D. (Frontiers in Behavioral Neuroscience, 2019)
Early-life stress (ELS) poses risks for developmental and mental health problems throughout the lifespan. More research is needed regarding how specific ELS experiences influence specific aspects of neurodevelopment. We examined the association between ELS, defined as severe adversity (e.g., domestic violence, caregiver drug use) and severe relational poverty (e.g., caregiver neglect, lack of caregiver attunement), occurring during the first two months of life and a variety of brain-related, clinician-rated functions, including self-regulation and relational capacities. Interdisciplinary clinicians using the Neurosequential Model of Therapeutics (NMT), an approach to clinical problem solving, reported on the timing and type of treatment-seeking children’s (N = 2,155; 8 to 10 years) stressful experiences during four developmental periods: Perinatal (0-2 mos), Infancy (2-12 mos), Early Childhood (13 mos to 4 years), and Childhood (4 to 11 years). They also reported on children’s current functioning in 32 brain-related domains (e.g., sleep, arousal, impulsivity, empathy, concrete cognition). Non-negative matrix factorization was conducted on the 32 brain-related domains to identify latent factors, yielding four factors comprising Sensory Integration, Self-Regulation, Relational, and Cognitive functioning. Regularized hierarchical models were then used to identify associations between ELS and each latent factor while controlling for stress occurring during subsequent developmental periods, and children’s current degree of relational health. ELS (stress occurring during the first two months of life), specifically a severe lack of positive relational experiences (e.g., caregiver neglect, lack of caregiver attunement), was associated with the Sensory Integration and Self-Regulation factors. The Relational factor was better explained by stress occurring during childhood, and the Cognitive factor by stress occurring during infancy and childhood. Implications for how the timing and type of stress experiences may influence brain-related outcomes that are observed in clinical settings are discussed. Future directions include longitudinal follow-ups and greater specification of environmental variables, such as types of interventions received and when they were received, that may interact with ELS experiences to influence brain-related outcomes.